2012
DOI: 10.18357/ijcyfs34.1201211557
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Developmental Assets in Ugandan Youth

Abstract: Ugandan youth face a number of threats to their healthy development including poverty, high rates of disease, civil conflict, and environmental degradation. Cultivating developmental competencies is critical, not only for youth, but also for the future of Ugandan communities and civil society. In this article, we highlight contextual challenges facing Ugandan youth, report exploratory results on “standard” measures of developmental assets, and discuss the utility of a positive youth development (PYD) framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…Youth in the present study reported better experience of internal than external assets. This result is also consistent with findings from other studies (Alvarado & Ricard, 2013;Drescher et al, 2012;Scales et al, 2012;Theokas et al, 2005). Majority of the youth in the present study (68.1%) reported internal assets in the adequate (53.8%) or good (14.3%) range but significant proportion of them (63.8%) were lacking external assets.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Youth in the present study reported better experience of internal than external assets. This result is also consistent with findings from other studies (Alvarado & Ricard, 2013;Drescher et al, 2012;Scales et al, 2012;Theokas et al, 2005). Majority of the youth in the present study (68.1%) reported internal assets in the adequate (53.8%) or good (14.3%) range but significant proportion of them (63.8%) were lacking external assets.…”
Section: Discussionsupporting
confidence: 93%
“…Girls reported statistically significantly higher mean scores on DAP, asset categories, and asset contexts than their counter part boys did. The finding is consistent with results of other international studies (Benson et al, 1999;Drescher et al, 2012;Leffert et al, 1998;Scales et al, 2005), although it was somewhat unanticipated given the status of women in Ethiopia. Historically Ethiopian females have been in disadvantage in many ways and are still facing numerous threats to their life including poverty, several forms of gender based violence, migration, and illiteracy to mention a few.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While developmental assets are mainly studied in US samples, the assets have also been reported in several non-US contexts, such as Albania, Bangladesh, Japan, Lebanon and the Philippines (Scales 2011), Italy, Norway and Turkey , Bulgaria and Kosovo (Wiium and Uka 2018) and Ghana (Wiium 2017). The present study is one of the few (e.g., Drescher et al 2012) reporting the assets among young people in sub-Saharan Africa. Therefore, the present findings extend the universality of the developmental assets.…”
Section: Discussionmentioning
confidence: 68%
“…First, a few of our participants were older than the usual adolescent groups that have been focused on in studies of the development assets. However, previous research has successfully studied the developmental assets where emerging adults, such as those involved in our study have been included (e.g., Drescher et al 2012;Scales 2011). Second, our participants are high school students who may not be representative of the youth population in the various countries.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%